Lung ultrasound to evaluate the outcome and prognosis of transient tachypnea of the newborn - Jiang, Peng; Wei, Jing; Han, Meiying (Frontiers in Pediatrics, 2025)
Background/ObjectivesTransient tachypnea of the newborn (TTN) is generally self-limiting. The increasing incidence of severe cases and lack of comprehensive studies on its clinical outcomes and influencing factors highlight the need for improved diagnostic and monitoring tools. This study aimed to assess the lung ultrasonographic features, recovery durations, and factors influencing TTN.MethodsTwo hundred neonates with wet lungs were selected as the TTN group and divided into mild (132/200) and severe (68/200) groups. Two hundred neonates without pulmonary disease served as controls. The acute-phase lung ultrasonographic features of the two groups were compared. According to the clinical recovery duration, TTN group was divided into group A (<5 days, 191/200) and group B (≥5 days, 9/200). Univariate and multivariate logistic regression analyses were used to analyze the relationship between clinically relevant factors and the recovery time.ResultsThe time that was required for the 200 neonates to fully recover without symptoms was 2.3 ± 1.33 days. The average clinical recovery durations of neonates with mild illness, those who required non-invasive ventilation, and those who required invasive ventilation were 1.42 ± 0.50, 3.36 ± 0.51, and 6.00 ± 1.12 days, respectively. The differences between the groups were significant (P < 0.05). Type II respiratory failure, acute respiratory distress syndrome (ARDS), persistent pulmonary hypertension of the newborn (PPHN), and heart failure were important factors affecting the recovery time.ConclusionThe lung ultrasonographic signs differed based on the degree of wet lungs. Moreover, type II respiratory failure, ARDS, PPHN, and heart failure are important factors prolonging the course of TTN in neonates.